Expression and clinical value of PD‐L1 which is regulated by BRD4 in tongue squamous cell carcinoma. Issue 2 (21st October 2019) - Zhao, Lu; Li, Pengchong; Zhao, Li; Wang, Miao; Tong, Dongdong; Meng, Zilin; Zhang, Qian; Li, Qing; Zhang, Fenghe
Abstract: The programmed cell death‐ligand‐1 (PD‐L1) and bromodomain protein 4 (BRD4) are frequently overexpressed in cancer and have even been shown to act synergistically. The aim of this study was to determine their potential oncogenic role .in tongue squamous cell carcinoma (TSCC). We detected significantly higher expression levels of both PD‐L1 and BRD4 in TSCC tissues compared to normal tissues ( P  ≤ .05). In addition, the high levels of PD‐L1 were significantly associated with increased tumor lymphatic metastasis ( P  ≤ .05), tumor staging ( P  ≤ .01), as well as BRD4 expression ( P  ≤ .05). Genetic and pharmacological inhibition of BRD4 in TSCC cells not only reduced their growth rate but also PD‐L1 levels ( P  ≤ .05), while overexpression of BRD4 upregulated PD‐L1. Bioinformatics analysis showed that c‐MYC and CDK9 were interactive partners of both BRD4 and PD‐L1. While c‐MYC clearly modulated the expression of PD‐L1, as well as reversed the inhibitory effects of JQ1, no obvious association was observed between CDK9 and PD‐L1. We report a novel regulatory axis consisting of BRD4, PD‐L1, and c‐MYC that likely drives TSCC progression, and is a potential prognostic marker and/or therapeutic target for TSCC. Abstract : We evaluated the expression and clinical value of programmed cell death‐ligand‐1 (PD‐L1) and bromodomain protein 4 (BRD4) in tongue squamous cell carcinoma (TSCC), and the relationship between them was studied. Then we report a novel regulatory axis consisting of BRD4, PD‐L1, and c‐MYC that likely drives TSCC progression, and is a potential prognostic marker and/or therapeutic target for TSCC.